PENGARUH GAYA KEPEMIMPINAN TERHADAP PRESTASI KERJA KARYAWAN PADA PERUSAHAAN PT. PULAU INDAH JAYA BANJARMASIN - Siti Mardah (Jurnal Ilmu Ekonomi dan Bisnis, 2020)
Abstract: The main factor supporting employee work performance is the leadership style applied by a company leader to employees who are subordinates to him. This is very closely related to the research I have made. Where the purpose of this study is to determine how much influence the leadership style has on achievement. Employee work in the company. Data collection techniques were taken from 60 employees of a total of 200 employees who were used as research samples. This study uses SPSS 16 as an analytical tool to measure validity, reliability, classical assumption test, simple linear regression. From this research it is obtained based on the results data processing, leadership style variables have a positive and significant effect on employee performance. In testing the hypothesis shows that the leadership style has a positive and significant effect on employee performance. The results of this research survey indicate that the work performance of employees that needs to be maintained is in the aspect where every job given to employees is done well and obtained satisfactory results so that it is profitable for the company. Keywords: Leadership Style, Job Performance